Predictors for Sedation Failure in Mitral Transcatheter Edge-to-Edge Repair Procedures - Christian Frerker; Malte Mathern; Roza Saraei; Christoph Marquetand; Tobias Graf; Mulham Alhagi; Thomas Stiermaier; Florian Genske; Dominik Jurczyk; Elias Rawish; Momir Dejanovikj; Friederike Foth; et al. (Journal of Interventional Cardiology)
Conclusions: Using DS in M-TEER is feasible with a low conversion rate to GA. In case of a conversion, the procedure is less successful regarding reduction of MR and more complications occurred with a lower survival rate up to 12 months. These data suggest that conversion from DS to GA is high risk. Therefore, we could identify different predictors for the need of a conversion to GA. However, our results could only be hypothesis-generated and should be evaluated in a randomized study.